Species Recognition Is Constrained by Chorus Noise, but Not Inconsistency in Signal Production, in Cope’s Gray Treefrog (Hyla chrysoscelis) - Tanner, Jessie C.; Bee, Mark A. (Frontiers in Ecology and Evolution, 2020)
Optimal mate choice based on the assessment of communication signals can be constrained by multiple sources of noise. One well-known impediment to acoustically guided mating decisions is the ambient noise created by multiple signaling individuals in large social groups, in which ambient noise can mask signals by impairing signal recognition and discrimination by receivers. Although studied far less often, another potential source of noise in communication systems stems from variability or inconsistency in how signalers produce their signals. Consistency is especially important in the context of mate choice because sexual advertisement signals are frequently produced repeatedly through time and are composed of constituent parts (e.g., notes, pulses) that are repeated within signals. Inconsistent signal production within individuals has the potential to mask between-individual differences that are often the target of receiver decision-making. In this study of Cope’s gray treefrog, Hyla chrysoscelis, we tested the hypothesis that ambient noise and inconsistent signaling, both independently and synergistically, impair discrimination of species identity. We assayed female discrimination based on pulse rate, a signal of species identity, in quiet and at three levels of ambient noise designed to simulate a breeding chorus. We used synthetic advertisement calls that were invariant or generated with one of three experimental levels of inconsistency in pulse rate, chosen based on levels of within-individual variation observed in natural calls. Pulse rate discrimination was impaired by average and above-average levels of chorus noise, but not by inconsistency in signal production. Receivers spent slightly more time making decisions at the highest level of chorus noise, but response latencies were unaffected by inconsistency. There was no evidence of synergism between ambient noise and inconsistency. Our results suggest that ambient noise, but not inconsistency in signal production, may limit sexual selection on a signal of species identity in natural settings.